Organización de la Bodega de Bienes y la Optimización del Espacio Físico de la Universidad Técnica de Babahoyo - Morán Herrera, Diego Armando (2017)
The Department of Property Control, Inventories of the Technical University of Babahoyo, said unit is responsible for the entry, storage and control of the goods that are purchased by the institution, seeks to distribute and store in a timely and adequate manner the merchandise following parameters that facilitate the logistics within the Warehouse of Goods